General self-efficacy and home-related problems of public high school students - Serrano, Mary Jean C.; Gabriel, Florenda S. (2005.)
The objective of this study is to provide a description of the home-related problems of public high school students and its relation to the strength of their general self-efficacy. Quantitative and qualitative design was used in the study. One hundred sixty nine students from tow public high schools participated in the survey. The survey instrument consisted of a scale to measure the strength of their self-efficacy and a scale to measure the prevalence of the different categories of home-related problems. Focused group discussion was conducted among 15 students to provide data for the home problems of strength of self-efficacy. The home-related problems are divided into four categories namely, problems regarding the different relationships in the family, problems regarding the role fulfillment of each family member, economic problems dealt with by the family, and the societal issues dealt with by the family. The most prevalent of the categories of home-related problems of public high school students, in decreasing order of prevalence, is as follows: problems regarding the different relationships in the family, followed by the problems regarding the role fulfillment of each family member, followed by economic problems, and followed lastly by problems falling under the category of societal issues. Despite these problems, the respondents possessed a moderately strong general self-efficacy. The kinds and prevalence of home-related problems of public high school students did not influence the strength of their general self-efficacy. The prevalence of the different categories of home-related problems is related with the overall degree of prevalence of home-related problems of public high school students. Furthermore, the different categories of home-related problems of public high school students are also related to each other.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: High school students -- Philippines; High school students -- Conduct of life